Hidden charm mesons in nuclear matter and nuclei - Cobos Martínez, J. J.; Tsushima, K.; Krein, G. [UNESP]; Thomas, A. W. (My University, 2022)
Recent results for the ηc- and J/ψ-nucleus bound state energies for various nuclei are presented. The attractive potentials for the ηc and J/ψ mesons in the nuclear medium originate, respectively, from the in-medium enhanced DD∗ and DD¯ loops in the ηc and J/ψ self energies. Our results suggest that the ηc and J/ψ mesons should form bound states with all the nuclei considered.